2021
DOI: 10.1002/ecs2.3715
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of flammability after a sequence of mixed‐severity wildfire in dry eucalypt forests of southern Australia

Abstract: Fire severity is the impact of a fire on the landscape, particularly the physical impact on vegetation. Previous studies have established that the severity of a fire can be influenced by the severity of previous fires. Many of these studies were conducted in mixed‐conifer forests, while little is known of this process in temperate eucalypt forests. Barker and Price in their 2018 publication (“Positive severity feedback between consecutive fires in dry eucalypt forests of southern Australia,” Ecosphere 9:e02110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…A recent study found that the median severity of prescribed burns in Eastern Australian eucalypt forests was 'high' (complete crown scorch, (Price et al 2022)), compared to a median severity of 'moderate' in wildfires for the same region (Collins et al 2021a). Given that positive severity feedbacks in that region have been most pronounced following high severity fire (Barker et al 2021), it is possible that a regime dominated by wildfires may have a less pronounced peak in flammability. Cultural burning practices have been shown to both consume less surface litter and burn at a significantly lower severity than prescribed burns (Price et al 2022), potentially reflecting their very small scale and locationspecificity (Lullfitz et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the median severity of prescribed burns in Eastern Australian eucalypt forests was 'high' (complete crown scorch, (Price et al 2022)), compared to a median severity of 'moderate' in wildfires for the same region (Collins et al 2021a). Given that positive severity feedbacks in that region have been most pronounced following high severity fire (Barker et al 2021), it is possible that a regime dominated by wildfires may have a less pronounced peak in flammability. Cultural burning practices have been shown to both consume less surface litter and burn at a significantly lower severity than prescribed burns (Price et al 2022), potentially reflecting their very small scale and locationspecificity (Lullfitz et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The land-use types have a significant impact on wildfire occurrence, as they influence vegetation characteristics, quantity, structure, and continuity, ultimately affecting the probability, spread rate, fire size, and environmental impacts of wildfires [52,84,85]. Generally speaking, forested, grassland, and farmland areas typically accumulate combustible vegetation, such as dry leaves and grass, making them more prone to fire occurrence and less equipped with natural and artificial fire prevention measures.…”
Section: Additional Explanation Of Wetland Wildfires In Central Chinamentioning
confidence: 99%